The Discourse of Normalcy and Deformity in the Victorian Novel: a Disability Studies' Perspective. - Hueso-Vasallo, Manuel (Comares, 2017)
The chapter deals with the way in which Victorian authors often used disabled characters as metaphors for larger socio-cultural concerns. In order to analyze this literary characteristic of the Victorian era, the chapter addresses two important texts of the period: Oscar Wilde's The Picture of Dorian Gray, and Robert Louis Stevenson's The Curious Case of Dr. Jekyll and Mr Hyde.
https://accesoabiertocomares.com/index.php/coa/politica
Keywords: Literatura inglesa - S. XIX; Personas con discapacidad - En la literatura; Disability studies; Victorian literature; Oscar Wilde; Foucault; Robert Louis Stevenson